Brain white matter integrity in heroin addicts during methadone maintenance treatment is related to relapse propensity. Issue 2 (24th January 2016) - Li, Wei; Zhu, Jia; Li, Qiang; Ye, Jianjun; Chen, Jiajie; Liu, Jierong; Li, Zhe; Li, Yongbin; Yan, Xuejiao; Wang, Yarong; Wang, Wei
Abstract: Introduction: Cognitive deficits caused by heroin‐induced white matter (WM) impairments hinder addicts' engagement in and benefit from treatment. The predictive value of WM integrity in heroin addicts during methadone maintenance treatment (MMT) for future relapse is unclear. Methods: Forty‐eight MMT patients were given baseline diffusion tensor imaging scans and divided into heroin relapsers (HR, 25 cases) and abstainers (HA, 23 cases) according to the results of 6‐month follow‐up. Intergroup comparisons were performed for fractional anisotropy (FA), radial diffusivity (RD), and axial diffusivity (AD). The correlation between diffusion tensor imaging indices and the degree of heroin relapse was analyzed. Results: Compared with HA group, HR group had reduced FA in the right retrolenticular part, left anterior and posterior limb of internal capsule, bilateral anterior corona radiata, and right external capsule. Three out of the six regions showed increased RD, with no changes in AD. The FA and AD values in the left posterior limb of internal capsule correlated negatively with the heroin‐positive urinalysis rate within follow‐up. Conclusions: Lower WM integrity in MMT patients may add to neurobiological factors associated with relapse to heroin use. Strategies for improving WM integrity provide a new perspective to prevent future relapse to heroin abuse. Abstract : Future heroin relapsers have lower white matter integrity compared to abstainers during methadone maintenance treatment. Lower white matter integrity is associated with higher frequency of relapse. Impairment of white matter integrity might underlie an increased risk for heroin relapse.